Desenvolvimento da interface e automatização da coleta de dados na Open Smart City View - Rigo, Fernanda (2018)
Along with the increase of cities’ population during the last decades, several challenges are found in governmental scope. The citizen is an important element in the process of building an intelligent city, based on the information and knowledge provided by open governmental data. If these data are handled and mined properly, they serve to empower the population and its part in decision making. Thus,the Open Smart City View (OSCV) architecture was designed and developed as a functional technological model for collecting, processing and presentating relevant information, from data collected in government transparency portals [1]. To further complement the functionalities present in the tool, a web crawler process was developed to perform the data collection automatically in the sources and portals. With this, the data warehouse is constantly updated with information. To evaluate the development of the extraction process, a functional test was performed using the JUnit framework to obtain the correct functioning of the implemented methods. Also, a clear and concise web interface has been developed for the visualization of the information collected and stored in the data warehouse by the tool. The interface is used to carry out queries and research on issues related to society, providing a better engagement of citizens with issues of their community. Through the SUS evaluation method, it is possible to evaluate the usability of the projected interface obtaining, after the tests performed, a result with a satisfactory score.